PRODUCTION OPTIMIZATION OF GRAPHENE OXIDE VIA ELECTROCHEMICAL EXFOLIATION - MOHD ZAID, AHMAD AMIR FARHAAN (IRC, 2017)
The objective of this study is to optimize the production of graphene oxide using electrochemical exfoliation method. Graphene is a 2D carbon sheet that bonded in the form of hexagonal honeycomb lattice [1]. Graphene is used in electronics industry for improvement in computing performance with 97.7% transparency [2]. Electrochemical exfoliation method is studied because it is economical method and it shows that the usage of pH controlled H2SO4 as the electrolyte increased the efficiency. Effects of voltage is also studied to optimize the results based on the previous research [3]–[7]. This study aims to determine the effect of H2SO4 pH and voltage on the mass produced for the optimization purposes. The FESEM and XRD characterization are implemented to prove the characteristic of produced graphene oxide flakes [6]–[7]. This study was optimized using Design Expert 10. To complete the study, the optimization primary result were generated using Central Composite Design – Response Surface Method available in Design expert 10. After the required parameter obtained, 13 electrochemical exfoliation experiments has been conducted and the experiment with highest mass graphene oxide produced is chosen for characterization. The selected sample was characterized using FESEM and XRD. As a result, the optimized values of electrolyte pH and applied voltage has been determined. The combination of lowest electrolyte pH and highest voltage applied will result in highest mass produced. The FESEM characterization shows the stacked layer of graphene oxide has been produced. The element present in the graphene oxide flakes was characterized using XRD. In conclusion, the relationship of electrolyte pH and voltage applied has been studied to optimize the production of graphene oxide using electrochemical exfoliation method. The type of characterization conducted was also suitable for this study.